Far right populism in Portugal: The political culture of Chega’s members - Marchi, R.; Zúquete, J. P. (Análise Social, 2024)
In 2019, Chega burst onto the Portuguese political scene, becoming the third most significant political force in the national parliament over the next four years. This article focuses on the political culture of Chega’s members and it aims to find if and how this political culture fits in with that of the populist radical right. To this end, an online survey (carried out between May 24th and June 16th of 2021) was distributed to party members addressing the following various dimensions. The 3,183 validated responses show a political culture that falls within the main lines of the radical right: nativism, authoritarianism, and populism. However, the distribution of the sample reveals less polarization than expected in the central themes of nativism (ethnic homogeneity) and populism (direct democracy).